A. VAN DIJK TEUN ANALYSIS IN SONTOLOYO POLITICAL DISCUSSION - Setia Ratna Dewi; Stevany Destriyana; Enung Nurhayati (IKIP Siliwangi, 2019)
News circulating lately refers to the president's statement which eventually becomes a discourse in every news. The sontoloyo politician is actually a quote from the president's statement which is the root of the problem. The author wants to analyze, how the process of production and acceptance of the discourse actually is. Therefore, the author determines the background of the problem in this study, namely 1) How Teun A. van Dijk's theory can influence the reader after reading the news based on the analysis model image and the schematic of the process of receiving information in electronic media republika.co.id and seconds. com ?; 2) What is the theory of Teun A. van Dijk's theory of the macro context and micro context elements contained in electronic news republika.co.id and pilpre.tempo.co ?; 3) What is the final conclusion that can be accepted by the reader after reading electronic news republika.co.id and detik.com using Teun A. van Dijk's theory through the macro context and micro context elements? The analytical tool in this study is to use Teun A. van Dijk's theory which refers to text formation images, information receipt charts, and macro and micro context analysis. The results of the analysis of this study are that the reading concept will mean reading, the results of the meaning will be analyzed by the reader by using the background of his knowledge. So, the media has a tendency to make things different, according to the interests and authorities who govern them. Readers must be able to sort out so that they are not easily affected by the formation of writing or framing made by the media.